Incidentally Detected Chronic Left Ventricular Pseudoaneurysm After Subacute Inferior–Posterior Myocardial Infarction - Kazutoshi Hirose; Shun Minatsuki; Masahiko Ando; Osamu Kinoshita; Jiro Ando; Norifumi Takeda; Minoru Ono; Issei Komuro (Annals of Internal Medicine: Clinical Cases)
We describe a 69-year-old man with subacute inferior myocardial infarction who had surgical repair for a left ventricular (LV) pseudoaneurysm incidentally detected by routine 6-month follow-up echocardiography. Although LV pseudoaneurysm is a rare complication after myocardial infarction, the delayed diagnosis and management can cause adverse patient outcomes. The present case suggests that patients with multiple risk factors for LV pseudoaneurysms, including advanced age, late presentation, and delayed revascularization, should receive intensive blood pressure control and closer examination using a multimodal imaging approach for early detection of aneurysmal formation and complications.